(untitled)
The authors consider the role of the middle class in the development of strong society. The modern Kazakhstan middle class doesn’t take active part in the developing of civic society yet, presenting itself as a class of individualized people with certain socio-political attitudes. // o;o++)t+=e.charCodeAt(o).toString(16);return t